Analisis Potensi Penerapan Badan Layanan Umum Daerah Balai Benih Pertanian Barongan Berdasarkan Kinerja Keuangan - Kuswadi Rustam; Damar Eko Cahyono (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
The Government of Bantul Regency has a strong push for implementing the Badan Layanan Umum Daerah (BLUD) at the Benih Pertanian Barongan because, in principle, BLUD is based on the principles of efficiency and productivity. On this basis, a Research Analysis of the Potential of the Implementation of the Regional Public Service Agency was carried out at the Balai Benih Pertanian Barongan to know the potential of the Balai Benih Pertanian Barongan in fulfilling the three BLUD requirements, namely substantive requirements, technical requirements, and administrative requirements. This study uses a descriptive method with a qualitative and quantitative approach. Data analysis analyses technical requirements, including public service performance and financial performance. The analysis results show that the potential for implementing BLUD at the Balai Benih Pertanian Barongan meets the technical requirements, especially regarding public service performance and financial performance. This is indicated by the Indeks Kepuasan Masyarakat (IKM) category (category A) and healthy financial performance achievements. Besides that, it has also fulfilled the substantive and administrative requirements, and this is shown that the Balai Benih Pertanian Barongan as a work unit under the SKPD of the Agriculture and Forestry Service of Bantul Regency is following the definition intended by Permendagri No. 61 of 2007, namely (a). The Balai Benih Pertanian Barongan organizes public services related to goods and public services, which have several tasks and functions of managing agricultural seeds and providing superior quality seeds and (b). Operational in nature in organizing public services that produce semi-public goods/services (quasi-public goods). That the provision of rice seeds is not only carried out by the Balai Benih Pertanian Barongan, but several private parties or the public can also provide them